THE ROLE OF SMALL BUSINESS IN DEVELOPMENT OF SERVICE INDUSTRY (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The paper scientifically proves the role and significance of small business in development of service industry, trough application of geographical and economic innovative approaches and methods. The issue is diccussed in the context of application of new types of service for satistying the newly formed demands of peole. Scientific analysis has revelaled the great potential of small business and the ways of its application.
Keywords: small business; enterprise; potential; demand; service; approach; method; analysis; assessment